2022-RA-141-ESGO Genomic characteristic analysis in squamous cell carcinoma and adenocarcinoma of cervix identifies Alpelisib as a therapeutic option for PIK3CA mutational cervical carcinoma. (20th October 2022) - Cao, Canhui; Wei, Ye; Lin, Shitong; Liu, Binhan; Cheng, Sheng; Zhu, Zhixian; Wu, Peng
Abstract : Introduction/Background: Cervical squamous cell carcinoma (CSCC) and cervical adenocarcinoma (CAdC) are the two most histological types in cervical carcinoma, with unequal outcomes and unclear mechanisms in tumor biology. We aim to explore the genomic characteristics between them and identify a promising target for cervical carcinoma. Methodology: We analyzed the genomic data of cervical carcinoma to identify genomic characteristics between SCC and CAdC. In vitro and in vivo assays were performed to testify the therapeutic effects of Alpelisib in PIK3CA mutational cervical carcinoma. Mutation analysis, Enrichment and pathway analysis, and co-immunoprecipitation were used to demonstrate the mechanisms of Alpelisib in cervical carcinoma. Results: CSCC showed higher point mutation density, high copy number cluster, low to intermediate CpG island methylator phenotype (CIMP) compared with CAdC, with the enrichment in the RTK/PI3K/MAPK pathway. In addition, point mutation of PIK3CA (P=0.0401) was significantly observed in CSCC, with different overall survival (P=0.0469) between the two histological types. In vitro, PIK3CA mutational cell lines (ME-180 and Ca-Ski) showed higher sensitivity to Alpelisib than cell lines without PIK3CA mutation. The correlation genes of PIK3CA in cervical cancer showed the enrichment of DNA replication and repair pathway. By performing co-immunoprecipitation, reduced interaction of p110α with ATR was found in cervical cancer cells with PIK3CA mutations, which made them sensitive to the combination of Alpelisib and cisplatin in vivo . Furthermore, we found that Alpelisib significantly suppressed tumor proliferation and migration in cervical carcinoma cells via inhibiting the AKT/mTOR pathway. Conclusion: Our study provides insights into the molecular characteristics between SCC and CAdC and identifies Alpelisib as a therapeutic option for PIK3CA mutational cervical carcinoma.